2011
DOI: 10.1615/intjmedmushr.v13.i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Wild Edible Mushrooms as Sources of Antioxidants

Abstract: The purpose of the study was to explore sixteen of the most popular edible species of wild-growing mushrooms as potential sources of antioxidants. Among the mushrooms tested, the highest total polyphenol contents, exceeding 100 mg/100 g fresh mass, were found in five mushrooms: Boletus chrysenteron, B. edulis, Leccinum scabrum, L. aurantiacum, and Macrolepiota procera. Antioxidant activity was measured with the FRAP, TEAC, DPPH scavenging ability and ferrous ions chelating ability assays. Results of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Whereas, the total flavonoid content for these food categories are: 2.5-76. [12][13][14][15][16]. In comparison to these plant foods assayed with the same procedure as in the current study, sprouts are comparable to most of vegetables, fruits and beverages with respect to FRAP antioxidant potential, polyphenol and flavonoid contents.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Whereas, the total flavonoid content for these food categories are: 2.5-76. [12][13][14][15][16]. In comparison to these plant foods assayed with the same procedure as in the current study, sprouts are comparable to most of vegetables, fruits and beverages with respect to FRAP antioxidant potential, polyphenol and flavonoid contents.…”
Section: Discussionmentioning
confidence: 65%
“…On the other side, the antioxidant power of some products has not been establish yet. Therefore, the present study evaluates antioxidant activity, as well as polyphenol and flavonoid contents, in common sprouts having an aim to extend our already published food databases [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, Witkowska et al . () demonstrated that S . grevillei possesses high antioxidant potential.…”
Section: Resultsmentioning
confidence: 99%
“…Many edible mushrooms have been found to exhibit anti-inflammatory properties due to the presence of some phenolic compounds ( Figure 5 ). For example, the common phenolic molecule pyrogallol has been extracted from Agaricus bisporus , Cantharellus cibarius , and Lactarius deliciosus [ 89 , 90 ]. Pyrogallol inhibited NO production and iNOS, IL-1 β , and IL6 mRNAs expression in response to LPS-stimulated RAW 364.7 macrophages [ 91 ].…”
Section: Anti-inflammatory Compounds Of Mushrooms and Modes Of Actmentioning
confidence: 99%